Mono‐, di‐ and trimethylated homologues of isoprenoid tetraether lipid cores in archaea and environmental samples: mass spectrometric identification and significance. (17th November 2015) - Knappy, Chris; Barillà, Daniela; Chong, James; Hodgson, Dominic; Morgan, Hugh; Suleman, Muhammad; Tan, Christine; Yao, Peng; Keely, Brendan
Abstract : Higher homologues of widely reported C86 isoprenoid diglycerol tetraether lipid cores, containing 0–6 cyclopentyl rings, have been identified in (hyper)thermophilic archaea, representing up to 21% of total tetraether lipids in the cells. Liquid chromatography‐tandem mass spectrometry confirms that the additional carbon atoms in the C87‐88 homologues are located in the etherified chains. Structures identified include dialkyl and monoalkyl ('H‐shaped') tetraethers containing C40‐42 or C81‐82 hydrocarbons, respectively, many representing novel compounds. Gas chromatography‐mass spectrometric analysis of hydrocarbons released from the lipid cores by ether cleavage suggests that the C40 chains are biphytanes and the C41 chains 13‐methylbiphytanes. Multiple isomers, having different chain combinations, were recognised among the dialkyl lipids. Methylated tetraethers are produced by Methanothermobacter thermautotrophicus in varying proportions depending on growth conditions, suggesting that methylation may be an adaptive mechanism to regulate cellular function. The detection of methylated lipids in Pyrobaculum sp. AQ1.S2 and Sulfolobus acidocaldarius represents the first reported occurrences in Crenarchaeota . Soils and aquatic sediments from geographically distinct mesotemperate environments that were screened for homologues contained monomethylated tetraethers, with di‐ and trimethylated structures being detected occasionally. The structural diversity and range of occurrences of the C87‐89 tetraethers highlight their potential as complementary biomarkers for archaea in natural environments. Copyright © 2015 John Wiley & Sons, Ltd.